The impact of exercise on the cognitive functioning of healthy older adults: A systematic review and meta-analysis - Kelly, Michelle E.; Loughrey, David; Lawlor, Brian A.; Robertson, Ian H.; Walsh, Cathal; Brennan, Sabina (Ageing research reviews, 2014)
•Epidemiological research suggests that exercise benefits cognitive function.•Evidence from RCTs on the impact of exercise on cognitive function is inconsistent.•Combined exercise types such as Tai Chi may benefit executive functioning of older adults.•Differences in participant profiles and exercise programmes contribute to discrepancies.•Standardisation of research designs is required to achieve comparable results. Data from epidemiological, cross-sectional, and neuroimaging research show a relationship between higher levels of exercise and reduced risk of cognitive decline but evidence from randomised controlled trials (RCTs) is less consistent. This review examines the impact of aerobic exercise, resistance training, and Tai Chi on the cognitive function of older adults without known cognitive impairment. We investigate explanations for inconsistent results across trials and discrepancies between evidence from RCTs and other research data. Twenty-five RCTs were included in the review. Meta-analysis results revealed significant improvements for resistance training compared to stretching/toning on measures of reasoning (p<0.005); and for Tai Chi compared to ‘no exercise’ controls on measures of attention (p<0.001) and processing speed (p<0.00001). There were no significant differences between exercise and controls on any of the remaining 26 comparisons. Results should be interpreted with caution however as differences in participant profiles, study design, exercise programmes, adherence rates, and outcome measures contribute to both discrepancies within the exercise research literature and inconsistent results across trials.